Scaling Agile in a Large Automotive Organization A case study focusing on five Agile ways of working in terms of homogeneous and heterogeneous implementation - Lindén, Johanna; Schér, Hanna (My University, 2023)
The automotive industry is facing mounting pressure to increase speed and flexibility, while simultaneously grappling with the exponential growth of software’s influence on their products. In response, industry players are looking towards the software industry’s methods for solutions. The implementation of Agile ways of working (WoW) holds the potential to deliver benefits, but scaling such WoW poses challenges and raises the question of their requisite levels of homogeneity or heterogeneity. Homogeneity refers to an uniform approach across all teams, while heterogeneity refers to customization of AgileWoW to meet the unique needs of each team. This thesis aims to gain insights into the organization’s current approach regarding five identified Agile WoW and to aid in addressing whether the implementation of each individual Agile WoW should be characterized by a predominant state of homogeneity or heterogeneity. A case study approach was chosen, involving qualitative interviews with Team Managers of Agile teams and Change Leaders in the R&D department at Volvo Cars. The discussion provides a comprehensive overview of the current approach with the identified Agile WoW, highlighting positive and negative effects, operational efficacy, and areas for improvement. The study also identifies four perspectives — Purpose, Time (timing/cadence), Method, and Structure — that influence the degree of homogeneous and heterogeneous implementation in Agile WoW. Consequently, six propositions are proposed, based on both the perspectives and the unique characteristics inherent to each Agile WoW. The study concludes that Agile WoW can exhibit varying degrees of homogeneous and heterogeneous implementation, depending on the specific Agile WoW’s purpose, timing, cadence, method, and structure. The propositions derived from the analysis serve as potential frameworks for future research and offer directions for investigating homogeneity and heterogeneity within different Agile WoW contexts.
Keywords: Agile development; Scaling Agile; Backlog management; Daily stand-up; PI planning; Retrospective; Demo; Homogeneity or heterogeneity of Agile ways of working; Challenges in large-scale Agile; Success factors in large-scale Agile